Treatment of stroke in aged male and female rats with Vepoloxamer and tPA reduces neurovascular damage - Zhang, Li; Luo, Hao; Li, Chao; Teng, Hua; Powell, Brianna; Lu, Mei; Chopp, Michael; Zhang, Zheng Gang (Frontiers in Neurology, 2023)
Stroke is a leading cause of death and disability worldwide, mainly affecting the elderly. Unfortunately, current treatments for acute ischemic stroke warrant improvement. To date, tissue plasminogen activator (tPA) is of limited use in stroke patients mainly due to its narrow therapeutic window and potential for hemorrhagic complication. The adjuvant treatment with Vepoloxamer, a purified amphipathic polymer has been shown to enhance the thrombolytic efficacy of tPA treatment in young adult male rats after embolic stroke. However, most stroke patients are aged; therefore, the current study investigated the therapeutic effect of the combined tPA and Vepoloxamer treatment in aged male and female rats subjected to embolic stroke. Methods: Male and female Wistar rats at 18 months of age were subjected to embolic middle cerebral artery occlusion and treated either with monotherapy of tPA or Vepoloxamer, a combination of these two agents, or saline at 4 hours after stroke onset. Neurological outcomes were evaluated with a battery of behavioral tests including adhesive removal, foot-fault, and modified neurological severity score tests at 1 and 7 days after stroke onset, followed by histopathological analysis of infarct volume. Residual clot size and vascular patency and integrity were analyzed. Results: The combination treatment with Vepoloxamer and tPA significantly reduced infarct volume and neurological deficits in male and female rats compared to rats treated with saline and the monotherapies of tPA and Vepoloxamer. While Vepoloxamer monotherapy moderately reduced neurological deficits, monotherapies with tPA and Vepoloxamer failed to reduce infarct volume compared to saline treatment. Furthermore, the combination treatment with tPA and Vepoloxamer accelerated thrombolysis, reduced ischemia and tPA-potentiated microvascular disruption, and concomitantly improved cerebrovascular integrity and perfusion in the male ischemic rats. Conclusions: Combination treatment with tPA and Vepoloxamer at 4h after stroke onset effectively reduces ischemic neurovascular damage by accelerating thrombolysis and reducing ischemia and tPA potentiated side effects in the aged rats. This funding suggests that the combination treatment with tPA and Vepoloxamer represents a promising strategy to potentially apply to the general population of stroke patients.